PENYEDIAAN TENAGA LISTRIK BAGI MASYARAKAT DUSUN TANETE DESA CENRANA BARU KABUPATEN MAROS PERSFEKTIF SIYASAH DUSTURIYAH - rsnarzk, Rasnawati; Rahmiati, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This research aims to find out how electricity is provided for the people of Tanete Hamlet, Cenrana Baru Village, Maros Regency, Siyasah Dusturiyah Perspective. The main problem is divided into several sub-problems, namely: How to Implement Regional Regulation Number 7 of 2014 Regarding the Supply of Electricity in Tanete Hamlet, Cenrana Baru Village, Maros Regency (Siyasah Dusturiyah Perspective) and what factors influence the Supply of Electricity in Tanete Hamlet, Cenrana Village New Maros Regency Siyasah Dusturiyah Perspective. The research method used is qualitative or field research. The results of this research show that in the implementation of Regional Regulation no. 7 of 2014 regarding the provision of electricity in Tanete Hamlet, Cenrana Baru Village, Maros Regency, has been running as expected by the community regarding the availability of electricity thanks to the efforts made Regional Government. If you look at Islamic teachings, providing electricity is a human problem. In procuring electricity in Tanete Hamlet because it talks about the responsibilities of a leader. The inhibiting factor is the delay in the procurement of electricity, which in the mailing system is slow to be handled by PLN due to changes in the system, access roads, and the costs required in building the electricity network are not in accordance with the profits that will be obtained by the PLN company.